District Land Office Purworejo Role in Efforts To Solve Grants Dispute (Case 32 / Pdt.G / 2018 / PN. Pwr) - Bayun Kismantoro; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The number of disputes in Purworejo regency, especially in the area of land would make the authors interested in examining disputes and conduct research on the consideration of the judges through decisions that have been stated. Land disputes, is anything that causes disagreements, discord or strife. Dispute is a continuation of the conflict, and the conflict itself is a dispute between two parties, but the dispute was only buried and can not be shown and when the dispute was notified to the other party will be disputed. The problems of this study are 1) How Purworejo District Land Office Role In Resolving Grants Disputes Efforts In Case No.32 / Pdt.G / 2018 / PN.Pwr, 2) How Consideration Judge In Case No.32 / Pdt.G / 2018 / PN.Pwr About Grant Dispute.This research used normative juridical approach (normative legal research) so called because this research is the study of literature. This study uses a basic decision No.32 / Pdt.G / 2018 / PN.Pwr. Normative research that discusses the doctrines or principles in jurisprudence. The results of this study show that, 1) Role of the District Land Office Purworejo In Effort Resolving Disputes Grant In Case No.32 / Pdt.G / 2018 / PN.Pwr rolegive evidence in the trial to support the strong evidence. 2) Consideration Judge In Case No.32 / Pdt.G / 2018 / PN.Pwr About Grant Dispute. Judge offers mediation in accordance initial steps of the Supreme Court Regulation No. 1 of 2016.Based on the results of data analysis concluded that give evidence in the trial to support the strong evidence in case of Grant Disputes from the District Land Office Purworejo, consideration of the judge that the plaintiff has successfully refute the arguments of gugatanya partly in what he demanded from the gugatanya. Then the judges verdict. Suggestions for Purworejo Land Office Hopes to be more careful in the process of registration certificates andSense of justice is extremely important for the judge to impose any decision.Keywords: Land Office; Legal Dispute; Grant.